2018
DOI: 10.3844/ajessp.2018.203.211
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Hazardous Medical Waste Generation Rates of Private Health Care Facilities-Case Study from Dhaka City of Bangladesh

Abstract: Many developing countries are lagging behind the developed countries to properly manage their hazardous healthcare waste. These waste pose a significant epidemiological risks to the general people. To estimate the epidemiological risks and to establish parameters of any waste management plan, quantitative estimation of healthcare waste generation is essential. Most researches on quantitative estimation of healthcare wastes to date, have not addressed the differences in waste generation trends between the gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In particular, water pollution from the industry and manufacturing sector, urban agricultural, and residential (e.g., fecal sludge) sources continue to threaten the public health advances gained from national WASH progress as well as overall economic development (Hassan et al, 2008;Asian Development Bank, 2015;Kibria et al, 2016). Key sources of water pollution in Dhaka include industrial effluent Kibria et al, 2016), household wastewater and on-site sanitation systems (Karn and Harada., 2001;Akter et al, 2017), inadequate sewerage and illegal connections (Karn and Harada., 2001;Akter et al, 2017), medical waste (Hassan et al, 2008;Rumi and Karim., 2018), and improper solid waste disposal (Yasmin and Rahman., 2017). These conditions are exacerbated by environmental changes that manifest at the local scale, such as increased severity of seasonal flooding, excess and less predictable rainfall, coastal and waterway erosion, and extreme heat events (Araos et al, 2016;Amjad, 2019;Sarker and Wu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, water pollution from the industry and manufacturing sector, urban agricultural, and residential (e.g., fecal sludge) sources continue to threaten the public health advances gained from national WASH progress as well as overall economic development (Hassan et al, 2008;Asian Development Bank, 2015;Kibria et al, 2016). Key sources of water pollution in Dhaka include industrial effluent Kibria et al, 2016), household wastewater and on-site sanitation systems (Karn and Harada., 2001;Akter et al, 2017), inadequate sewerage and illegal connections (Karn and Harada., 2001;Akter et al, 2017), medical waste (Hassan et al, 2008;Rumi and Karim., 2018), and improper solid waste disposal (Yasmin and Rahman., 2017). These conditions are exacerbated by environmental changes that manifest at the local scale, such as increased severity of seasonal flooding, excess and less predictable rainfall, coastal and waterway erosion, and extreme heat events (Araos et al, 2016;Amjad, 2019;Sarker and Wu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have been carried out on medical waste management in Bangladesh, which mostly focused on the amount of waste that is produced by hospitals and the knowledge and attitude of healthcare workers about hospital waste [8,9]. A cross-sectional study conducted on nurses at Faridpur Medical College Hospital found that only 8% of the respondents had a sound knowledge of pharmaceutical wastes and only 7% could answer questions about biomedical wastes [10].…”
Section: Introductionmentioning
confidence: 99%